Two new species of Monogenea(Platyhelminthes: Cercomeridea) parasitic of Chaetodipterus faber (Teleostei: Epbippidae) from the Brazilian coastal zone - A. D., Cezar (1999)
Metazoan parasites were extracted for 110 Chaetodipterus faber (Broussonet, 1782) (Teleostei: Ephippidae) specimens from the coastal zone ofthe State of Rio de Janeiro, Brazil (nearly 21-23° S, 41-45°W). Two new species of monogeneans belonging to genera Sprostoniella and Parancylodiscoides are described and illustrated. The new species of Sprostoniella, differ from S. multitestis, the only kuown species of the genus, by: 1. the arrangement of septa (with 17 septa, two of them bifid and two incomplet in the new species; 17 septa, two of them trifid in S. multitestis). 2. the new species showed two central loculi, while S. multitestis only one, and 3. the first pair of anchors of the new species is small and poorly developed, while in S. multitestis is well developed and strong. The new species of Parancylodiscoides differs from P. chaetodipteri, the only kuown species of the genus, by: 1. the testis shape (bilobated in the new species, not bilobated in P. chaetodipteri), and 2. by the presence of accessory prostatie reservoir at the copnlatory organ base (absent in P. chaetodipteri).